2013
DOI: 10.1371/journal.pone.0084172
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biochemical Analyses of CbCel9A/Cel48A, a Highly Secreted Multi-Modular Cellulase by Caldicellulosiruptor bescii during Growth on Crystalline Cellulose

Abstract: During growth on crystalline cellulose, the thermophilic bacterium Caldicellulosiruptor bescii secretes several cellulose-degrading enzymes. Among these enzymes is CelA (CbCel9A/Cel48A), which is reported as the most highly secreted cellulolytic enzyme in this bacterium. CbCel9A/Cel48A is a large multi-modular polypeptide, composed of an N-terminal catalytic glycoside hydrolase family 9 (GH9) module and a C-terminal GH48 catalytic module that are separated by a family 3c carbohydrate-binding module (CBM3c) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 52 publications
7
74
1
2
Order By: Relevance
“…This specific activity of CbXyn10C is, however, very similar and comparable to that of GH9/CBM3c module of CelA recombinantly expressed in E. coli (6). As has been observed by Zverlov et al, CelA has posttranslational modifications (22) which were regarded to be responsible for the observed difference in the specific activities between natural and recombinant CelA proteins and its truncation mutants (6). The substrate competition experiment suggested that CbXyn-10C most likely harbors only one catalytic center.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This specific activity of CbXyn10C is, however, very similar and comparable to that of GH9/CBM3c module of CelA recombinantly expressed in E. coli (6). As has been observed by Zverlov et al, CelA has posttranslational modifications (22) which were regarded to be responsible for the observed difference in the specific activities between natural and recombinant CelA proteins and its truncation mutants (6). The substrate competition experiment suggested that CbXyn-10C most likely harbors only one catalytic center.…”
Section: Discussionsupporting
confidence: 73%
“…1E), as determined using beech wood xylan as the substrate. The thermophilic character of CbXyn10C is similar to that of other functionally characterized C. bescii glycoside hydrolases (4,6,22). Since C. bescii is a hyperthermophilic bacterium, this is not unexpected.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Understanding the novel lignocellulolytic enzymes within this genus is important for achieving higher levels of fermentable saccharides (13). The results seen with a unique multimodular glycoside hydrolase, CelA, which functions as a bifunctional exo-and endo-glucanase, are comparable to or better than those seen with current commercial cellulase formulations (30,31). However, branched hemicelluloses, such as arabino-xylan, restrict the complete enzymatic hydrolysis of lignocellulosic biomasses.…”
Section: Discussionmentioning
confidence: 99%
“…The major enzymes are composed of multidomain structures, two GHs, and one to three CBMs (13,14,16,17). Several multidomain enzymes have been biochemically characterized (18)(19)(20)(21)(22)(23). Nevertheless, the function and biochemical properties of noncatalytic proteins secreted by Caldicellulosiruptor species are unknown.…”
mentioning
confidence: 99%